KEPEMIMPINAN KEPALA DESA UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR DESA SALO KECAMATAN SALO KABUPATEN KAMPAR TAHUN 2023 - 2024 - Kurniawan, Firman; ,, Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Leadership at the village level plays an important role in encouraging community participation in village infrastructure development. In Salo Village, the success of village infrastructure development is greatly influenced by the village head's ability to build communication and the spirit of community participation. However, community participation is still relatively low, especially in the implementation stage of village infrastructure development. This is caused by the community's misunderstanding of village funds and a lack of awareness of the benefits of planned development. This study aims to describe the leadership of the Salo Village Head to increase community participation in infrastructure development in Salo Village, Salo District, Kampar Regency in 2023-2024. This study uses a qualitative approach with a descriptive method. The results show that the Head of Salo Village, Mr. Ihfasni Arham, M.Ag, applies five leadership indicators based on the theory of Rivai and Dedy (2012), namely: (1) the ability to foster cooperation and good relationships, (2) the ability to be effective, (3) participatory leadership (4) the ability to delegate tasks and time, and (5) the ability to delegate tasks and authority. The conclusion of this study is that the leadership of the Salo Village Head has succeeded in creating an environment that encourages community participation, although challenges remain in increasing awareness and active involvement. The research recommends that the village government increase outreach and education on the importance of participation and strengthen community empowerment through training and economic programs. Keywords: Leadership, Participation, Development, Village Head